1991
DOI: 10.1111/j.1399-6576.1991.tb03255.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pulmonary complications and lung function in high‐risk patients: a comparison of three physiotherapy regimens after upper abdominal surgery in general anesthesia

Abstract: The effect of three postoperative regimens of respiratory therapy on pulmonary complications and lung function was compared in high-risk patients. Fifty-one patients were randomized to: 1) conventional chest physiotherapy alone (PHYS), 2) chest physiotherapy and positive expiratory pressure (PEP), or 3) chest physiotherapy with both positive expiratory pressure and inspiratory resistance (RMT). Treatments were given twice daily by a physiotherapist and self-administered. The incidence of postoperative pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 24 publications
3
43
1
1
Order By: Relevance
“…1,2 The reported incidence of PPCs ranges from 10% to 88%, depending on the definition used and the population studied. [1][2][3][4][5][6][7][8] The incidence of PPCs also depends on the procedure and on individual patients' postoperative risk factors. 1 Compared to peripheral surgery, thoracic and upper abdominal surgeries result in the highest incidence of PPCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The reported incidence of PPCs ranges from 10% to 88%, depending on the definition used and the population studied. [1][2][3][4][5][6][7][8] The incidence of PPCs also depends on the procedure and on individual patients' postoperative risk factors. 1 Compared to peripheral surgery, thoracic and upper abdominal surgeries result in the highest incidence of PPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Breathing exercises and early mobilization are cornerstones of postoperative management. 2,4,10,13,[20][21][22][23] Early mobility following surgery is deemed crucial, since postoperative immobilization is widely held to contribute to cardiovascular instability, 10 thromboembolic complications, 24 and catabolism, 10 in addition to pulmonary morbidity. 25 Sitting out of bed has been shown to be associated with an increase in postoperative functional residual capacity, 25 and it has been suggested that a programme of active enforced progressive mobilization can improve pulmonary function following colon resection.…”
Section: Introductionmentioning
confidence: 99%
“…return to pre-operative respiratory status [6][7][8][9]. Another development in the care of post-operative patients is the change of routines concerning mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, treatments have changed, becoming more active, whereby the patients are encouraged to carry out a larger part of the training by themselves [6,7]. The use of deep breathing exercises has developed with the introduction of different breathing devices, including incentive spirometry and positive expiratory pressure (PEP), to facilitate breathing post-operatively and to accelerate the…”
mentioning
confidence: 99%
“…[10][11][12] The effects of different chest physiotherapy regimens have been evaluated among high-risk postoperative patients and none of them could be considered highly satisfactory with regard to preventing such complications. 13 On the other hand, preoperative chest physiotherapy reduced the incidence of postoperative pulmonary complications and improved mobilization and oxygen-hemoglobin saturation after major abdominal surgery. 14 The hypothesis of this study was that chest physiotherapy during the immediate postoperative period among patients who had undergone upper abdominal surgery would improve the postoperative results or prevent postoperative pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%